A animação sociocultural e a educação para o lazer nos tempos de HIV/AIDS - Herold, Patrícia (2011)
Since the emergence and identification of the first cases of HIV, AIDS is a major public health problem, globally speaking. Much progress has occurred in relation to antiretroviral treatment; however, as time passes, new challenges arise. Among these issues, one leads to the making of this thesis: the commitment of the social relations of PLHIV who are impacted by the discovery of contamination. It is assumed as a premise that leisure and SCA are possibilities on educational action on the horizon of self-care and human emancipation. Thus, the objective is to understand how the concepts and practices of leisure for people living with HIV /AIDS, may be influenced by the assumptions made by the SCA, contributing to the education for and by leisure. The work began with observations and interviews with the purpose of inclusion in the reality of PLHIV, demystifying some "pre" concepts and expanding the knowledge on the subject. Later, under the influence of participatory research, interventions were performed with other activities, based on the ideas advocated by the SCA. Regarding the analysis, autonomy and self-care were taken as significant categories for reflection. Thus, the study showed that education and the leisure from the perspective of the SCA can be used as an important tool in the fight against the deterioration of personal and social relationships arising from HIV / AIDS.